Outsourcing trust to the information infrastructure in schools: How search engines order knowledge in education practices. Issue 6 (10th October 2016) - Sundin, Olof; Carlsson, Hanna
Abstract : Purpose: This paper investigates the experiences of school teachers of supporting pupils and their apprehensions of how pupils search and assess information when search engines have become a technology of literacy in schools. By situating technologies of literacy as sociomaterial the purpose of this paper is to analyse and discuss these experiences and understandings in order to challenge dominant views of search in information literacy research. Design/methodology/approach: Six focus group interviews with in total 39 teachers working at four different elementary and secondary schools were conducted in the autumn of 2014. Analysis was done using a sociomaterial perspective, which provides tools for understanding how pupils and teachers interact with and are demanded to translate their interest to technologies of literacy, in this case search engines, such as Google. Findings: The teachers expressed difficulties of conceptualizing search as something they could teach. When they did, search was most often identified as a practical skill. A critical perspective on search, recognizing the role of Google as a dominant part of the information infrastructure and a co-constructor of what there is to know was largely lacking. As a consequence of this neglected responsibility of teaching search, critical assessment of online information was conflated with Google's relevance ranking. Originality/value: The study develops a critical understanding of the role of searching and search engines as technologies of literacy in relation to critical assessment in schools. This is of value for information literacy training.